GLOBALIZATION, INTERNATIONAL TRADE, AND POVERTY - Khaerudin, Khaerudin; Apriansyah, Nopri; Nabila, Nahla (Bina Bangsa International Journal of Business and Management, 2024)
Globalization and international trade have become key factors in the development of the global economy, yet their impact on poverty remains a subject of debate. This study aims to analyze the relationship between globalization, international trade, and poverty, as well as the effects on wealth distribution. Globalization, which involves the integration of economic, social, and cultural aspects across nations, creates opportunities for economic growth through increased flows of goods, services, and investments. However, its effects on developing countries tend to be uneven, with certain sectors experiencing rapid progress, while others lag behind, exacerbating social and economic inequality. International trade, although offering opportunities for income growth, also contributes to a greater divide between developed and developing nations. This research finds that while globalization can enhance long-term welfare, its uneven distribution worsens poverty in less-developed sectors. Therefore, this study recommends policies that support infrastructure development, strengthen inclusive trade policies, and empower vulnerable sectors to optimally utilize the potential of globalization.